Hazardous Substances Risk Prevention Procedures in Detergents Manufacturing Facilities: Case Study Teba Manufacture - Abu Sharakh, Sabah Ahmed Mahmoud; Al-Ashqar, Nizam Mahmoud; Al - Mughair, Mohammed Mohammed (Journal of Risk and Crisis Management, 2019)
The study aimed to identify the hazardous raw materials used in the Teba Manufactureand to indicate the preventive measures to deal with the risk of hazardous materials in the detergent manufactures. To achieve this aim، the researchers used the descriptive analytical approach to describe the preventive measures used in the Teba Manufacture، Analysis and effective planning to deal with the risk of hazardous materials through field visit and direct observation and interviews with stakeholders. The researchers reached a number of results، the most important of which is need for periodic inspection of hazardous facilities. The Manufacture works on the implementation of prevention and safety measures under difficult economic conditions. The researchers recommended to develop risk management mechanisms for hazardous materials in industrial facilities and to provide vapors for the process of manufacturing.